Cotton swabs for the measurement of NF-ĸB, IFN-γ, and FOXP3+Treg from lesions of anogenital wart patients - Hutabarat, Hernayati; Bramono, Kusmarinah; Indriatmi, Wresti; Wibowo, Heri; Budianti, Windy Keumala; Suyatna, Fransiscus Dhyanagiri; Prihartono, Joedo; Mawardi, Prasetya (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Local tissue immunity plays a significant role in anogenital warts’ (AGW) pathomechanism and persistence. Assessing biomarkers from lesions instead of serum is recommended to evaluate therapeutic response. Since biopsy is invasive, it is necessary to find less invasive and more comfortable methods. This study aimed to assess the reliability of cotton swabs and tape stripping for evaluating AGW’s lesions biomarkers. METHODS We compared cotton swab versus tape stripping method to quantify nuclear factor-κappaB (NF-ĸB), interferon-gamma (IFN-γ), and FOXP3+regulatory T cell (FOXP3+Treg) from 3 patients with AGW in the preliminary study. The method was selected based on contamination possibility, side effects, and a simpler approach. The main study examined 48 patients with AGW for reliability and reproducibility using the best sampling method from preliminary result and Spearman’s Rho analysis, while considering the HIV status and CD4+ counts. RESULTS Both cotton swabs and tape stripping obtained adequate protein content for biomarkers examination. However, the tape stripping method was causing serum contamination and painful for patients due to the stripping. The total lesion volume in cotton swab method was positively correlated with all patients’ NF-ĸB (p = 0.001). IFN-γ had a negative correlation in all reactive HIV patients (p = 0.012). FOXP3+Treg and CD4+ counts were negatively correlated with total volume in reactive HIV patients (p = 0.046 and 0.017, respectively). CONCLUSIONS The cotton swab method was reliable in examining NF-ĸB, IFN-γ, and FOXP3+Treg due to its convenience and lack of serum contamination from AGW lesions, potentially improving patient comfort and practical benefits.